PENERAPAN KLAUSUL PILIHAN YURISDIKSI (CHOICE OF JURIDICTION) DAN PILIHAN HUKUM (CHOICE OF LAW) DALAM PENYELESAIAN SENGKETA BISNIS INTERNASIONAL (Studi Kasus: Perkara PT. Symrise melawan PT. Mega Suryamas) - Cut Memi (Faculty of Law - Tarumanagara University, 2017)
The aims of this research are to examine the practice of applying the choice of jurisdiction and choice of law in the settlement of business dispute between PT. Symrise and PT. Mega Suryamas in South Jakarta District Court and to examine the validity of the arbitration agreement contained in the Invoice. In relation to the problem studied is the norm, then in this study, the method used is the method of normative legal research or normative juridical. The legal substance used in this study is the primary legal material which includes the legislation regarding the arbitration, the court decision, the provisions of the international convention on arbitration, the opinions of experts (doctrine) obtained through the literature, as well as non-legal materials in the form of records of interviews with experts and customs applied in legal practice, especially in the settlement of international arbitration disputes. This research is expected to contribute to the development in the field of law, especially in the application of choice of jurisdiction and choice of law in the settlement of international business disputes in Indonesia.Keywords: choice of jurisdiction, choice of law, international business disputes in Indonesia